Cryptochromes are the dominant photoreceptors mediating heliotropic responses of Arabidopsis inflorescences. (10th July 2021) - Serrano, Alejandro Miguel; Vanhaelewyn, Lucas; Vandenbussche, Filip; Boccalandro, Hernán Esteban; Maldonado, Belén; Van Der Straeten, Dominique; Ballaré, Carlos Luis; Arana, María Verónica
Abstract: Inflorescence movements in response to natural gradients of sunlight are frequently observed in the plant kingdom and are suggested to contribute to reproductive success. Although the physiological and molecular bases of light‐mediated tropisms in vegetative organs have been thoroughly investigated, the mechanisms that control inflorescence orientation in response to light gradients under natural conditions are not well understood. In this work, we have used a combination of laboratory and field experiments to investigate light‐mediated re‐orientation of Arabidopsis thaliana inflorescences. We show that inflorescence phototropism is promoted by photons in the UV and blue spectral range (≤500 nm) and depends on multiple photoreceptor families. Experiments under controlled conditions show that UVR8 is the main photoreceptor mediating the phototropic response to narrowband UV‐B radiation, and phototropins and cryptochromes control the response to narrowband blue light. Interestingly, whereas phototropins mediate bending in response to low irradiances of blue, cryptochromes are the principal photoreceptors acting at high irradiances. Moreover, phototropins negatively regulate the action of cryptochromes at high irradiances of blue light. Experiments under natural field conditions demonstrate that cryptochromes are the principal photoreceptors acting in the promotion of the heliotropic response of inflorescences under full sunlight. Abstract : We investigated the phototropic response of A. thaliana inflorescences in the laboratory and in the field. Under natural conditions, plants displayed heliotropic inflorescences. The heliotropic response under full sunlight was activated by UV‐A/blue light photons, acting through the cryptochromes.